Development of the Computer Graphics Management System Using Text of Natural Language - Al Salaimeh S. (Журнал інженерних наук)
The computer has been an integral part of our life. We cannot imagine complicated mathematical and technological calculation without using computer, but we are at this stage in the development of computing systems, when is not enough computer obedience. We needed an assistant. In this paper, we can see the predicate presentation of the text of the natural language personal computer is able to understand person and obey his command. As for the scope of this method of representing natural language text, it is seen the first time that is the use spectrum is very large; firstly, it can be used for research and educational purposes, as well as to study algebra of predicates. Secondly, use as an assistant in the word a user with a computer (is a good addition to the programs engaged in speech recognition). Thirdly, in the regions associated with artificial intelligence.